2015
DOI: 10.7202/1029426ar
|View full text |Cite
|
Sign up to set email alerts
|

Teaching for Transfer: Insights from theory and practices in primary-level French-second-language classrooms

Abstract: This paper illustrates teaching for transfer across languages by synthesizing key insights from theory and previously published research alongside our case study data from primary-level teachers in core French-second-language (CF) classrooms in Ontario, Canada. Drawing on research that redefines language transfer as a resource, this study drew on several influential theoretical notions and data collected through interviews and classroom observations. All of these sources point to a multi-leveled approach to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Within the field of FSL education, much of what is understood to be true about teacher perceptions of core French and French immersion programs and about the students enrolled in these courses has been largely anecdotal. Though there have been smaller studies-usually at the scale of a case study or exploratory case study-that have queried the beliefs and perceptions of the teachers who have been under consideration (e.g., Knouzi & Mady, 2014;Thomas & Mady, 2014), only one formal study has considered the views and, to some degree, the experiences of FSL teachers across Canada.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within the field of FSL education, much of what is understood to be true about teacher perceptions of core French and French immersion programs and about the students enrolled in these courses has been largely anecdotal. Though there have been smaller studies-usually at the scale of a case study or exploratory case study-that have queried the beliefs and perceptions of the teachers who have been under consideration (e.g., Knouzi & Mady, 2014;Thomas & Mady, 2014), only one formal study has considered the views and, to some degree, the experiences of FSL teachers across Canada.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They will also shed light on another question Padden raised that is more pedagogical in nature, that is, "how might a sign and a spoken language be organized together as a means of educating young deaf children?" by showing what sign language competences could and should perhaps be capitalized on to promote d/Deaf children's literacy development through "teaching for transfer" (Ballinger et al, 2020;Cummins, 2021;Thomas & Mady, 2014).…”
Section: Sign Language In D/deaf Students' Spoken/written Language De...mentioning
confidence: 99%
“…For example, observations by Simard and Jean (2011) showed that grammar-oriented interventions are a dominant part of FSL teaching when compared to English as a second language (ESL) teaching in the Canadian context (in this case, Quebec). Precise ways in which both CF and FI teachers can capitalize on students' existing language knowledge in order to promote transfer between languages have also been described in detail (Arnott & Mady, 2013;Cammarata & Haley, 2017;Thomas & Mady, 2014;Vandergrift, 2006). Researchers have used these findings to make suggestions about what is indeed pedagogically possible (or not) in the K-12 FSL context.…”
Section: French Language Instruction (Fli)mentioning
confidence: 99%
“…Setting aside the impact of pedagogy on student learning, a smaller proportion of the studies documenting FSL teacher practices included a complementary analysis of teacher perspectives on their FSL pedagogy, which offered additional explanations for what the researchers had observed. For example, interviews revealed that CF teachers specifically plan for transfer (Thomas & Mady, 2014) and that collaboration and coplanning are key to implementing literacy-based practices in this context (Arnott & Mady, 2013). Other researchers used interviews to conclude that teacher beliefs had a major influence on the FSL teacher practices that were observed (e.g., Arnett, 2010;Arnott, 2011).…”
Section: French Language Instruction (Fli)mentioning
confidence: 99%